DRINKING WATER QUALITY BY THE USE OF CONGO RED MEDIUM TO DIFFERENTIATE BETWEEN PATHOGENIC AND NON PATHOGENIC E. coli AT POULTRY FARMS - M. D. Ahmad; R. A. Hashmi; A. A. Anjum; A. Hanif; R. H. Ratyal (Journal of Animal and Plant Sciences, 2009)
Keeping in view the importance of drinking water and its effect on poultry performance, 86 water samples from 55 poultry farms were collected to determine the presence and pathogenicity of Escherichia coli. All samples were cultured on MacConkey’s agar plates. The positive samples were examined for fecal coliform. Identification of E. coli was carried out on the basis of microscopic, cultural and biochemical characteristics. In vitro pathogenicity test for E. coli was conducted by using Congo red binding activity. Out of 86 water samples processed for coliform, 73 produced growth on MacConkey’s agar. Indole test and biochemical reactions identified 26 of these as E. coli. Out of 26 isolates of E. coli, 20 resulted in the growth of brick red colored colonies indicative of pathogenic nature where as the remaining 6 produced grayish white colonies after 96 hours of growth and were considered as non pathogenic.
Keywords: Escherichia coli; drinking water; coliform; Congo Red; Pathogenicity